MENINGKATKAN KETERAMPILAN MOTORIK KASAR GERAK MANIPULATIF ANAK USIA 4-5 TAHUN - Susanthi Pradini; Sugiana; Dwi Jayanti Kurnia Dewi; Tommy Rizki Prasetyo (Jurusan Ilmu Pendidikan - Universitas Lampung, 2022)
The number of kindergarten teachers who have difficulty in providing activities to develop gross motor skills in their students. Based on these problems, this service aims to improve the ability of teachers to provide gross motor learning activities, especially manipulative movements for early childhood. This service is designed with the following steps: 1) initial design; 2) prepare manual manual for gross motor manipulative motion; 3) training; 4) evaluation of training activities; 5) implementation of manual manual manual manipulative movements of children aged 4-5 years. The results of this dedication indicate that gross motor training of manipulative movements for children aged 4-5 years for kindergarten teachers is very effective for kindergarten teachers. This can be explained by the difference in the mean results of the pre-test and post-test of 36. Which means that there is an increase in the knowledge and skills of kindergarten teachers regarding gross motor skills of manipulative movements, with increasing teacher skills, the gross motor skills of students also increase.